Calculation of vibrational energy of molecule using coupled cluster linear response theory in bosonic representation: convergence studies - Banik, Subrata; Pal, Sourav; Prasad, M. Durga (Journal of Chemical Physics, 2008)
Vibrational excited state energies have been calculated using vibrational coupled cluster linear response theory (CCLRT). The method has been implemented on formaldehyde and water molecule. Convergence studies have been shown with varying the cluster operator from S(4) to S(6) as well as the excitation operator from four bosons to six bosons. A good agreement with full configuration interaction results has been observed with S(6) truncation at coupled-cluster method level and six bosonic excitations at CCLRT level. (C) 2008 American Institute of Physics.

Calculation of dipole transition matrix elements and expectation values by vibrational coupled cluster method - Banik, Subrata; Pal, Sourav; Prasad, M. Durga (Journal of Chemical Theory and Computation, 2010)
An effective operator approach based on the coupled cluster method is described and applied to calculate vibrational expectation values and absolute transition matrix elements. Coupled cluster linear response theory (CCLRT) is used to calculate excited states. The convergence pattern of these properties with the rank of the excitation operator is studied. The method is applied to a water molecule. Arponen-type double similarity transformation in extended coupled cluster (ECCM) framework is also used to generate an effective operator, and the convergence pattern of these properties is compared to the normal coupled cluster (NCCM) approach. It is found that the coupled cluster method provides an accurate description of these quantities for low lying vibrational excited states. The ECCM provides a significant improvement for the calculation of the transition matrix elements.